Strategi Pengembangan Usaha Kedai Kopi Karakter Kopi di Kecamatan Denpasar Selatan Kota Denpasar (Jurnal Agribisnis dan Agrowisata, 2025)
Coffee Shop Business Development Strategy Karakter Kopi In South Denpasar District, Denpasar City. Karakter Kopi is one of the most popular coffee shops in Tukad Barito area. Karakter Coffee challenge is the increasing number of new coffee shop competitors, so it is necessary to develop a business strategy to increase competitiveness. The research was conducted at Kopi Character in South Denpasar from February to April 2023. The number of key informants was 15 informants, the data were analyzed descriptively based on the IFAS, EFAS, IE Matrix and SWOT Matrix methods. The aims of this research are: 1) Identify what are the internal and external factors that effects Karakter Kopi's business development 2) Analyzing the grand strategy in developing Karakter Kopi's business, and 3) Analyze the alternative strategies that can be applied.  The research results are as follows: 1) The internal factor that becomes the main strength of Karakter Kopi is the unique and strong concept, while the weakness of Karakter Kopi is the relatively higher price compared to nearby competitors. The external factor that becomes the main opportunity for Karakter Kopiis the high public interest in coffee. Meanwhile, the strongest threat that Karakter Kopi gets is the ever-increasing price of basic commodities. 2) The results of the study show that the company's position is in cell II so that the grand strategy that should be used are product development, market development and market penetration strategy. 3) The alternative strategy obtained from the SWOT matrix analysis are; S-O Strategy (Strength-Opportunities), WO Strategy (Weakness Opportunities), ST Strategy (strengths-threats), WT Strategy (weaknesses-threats).
Keywords: coffee Shop; bussiness; strategy; development